Framework for Designing Project Delivery and Contract Strategy in Chinese Construction Industry Based on Value-Added Analysis - Jiyong Ding; Na Wang; Leichuang Hu (Advances in Civil Engineering)
A project delivery method (PDM) and project contract strategy (PCS) are two critical factors for project success in construction industry. Currently, there are several options available for them in the construction industry, with several innovative PDMs and PCSs emerging along with the development of the industry. This paper maintains that the PDM should be designed in combination with the PCS given their close relationship. This paper focuses on the design of project delivery and contract strategy (PDCS), with the aim of developing a conceptual framework for the PDCS design. The design process is divided into two stages: preliminary design and detailed design, taking engineering design as a frame of reference. In the design process, the value-added analysis of project objectives is adopted as a tool to make decisions at different stages. The framework proposed in this paper is intended to provide a more distinct and direct path to improving PDCS selection or design, as well as enhancing the reliability of decision-making.